Effect of surface treatments on color stability of lithium disilicate: a systematic review and meta-analysis - Alawawda, Osayd; Yanıkoglu, Nuran; Akıncı, Ilgınsu; Uzun, Merve (Journal of Stomatology, 2025)
This systematic review and meta-analysis aimed to evaluate the effect of surface treatments, polishing, and glazing on the color stability of lithium disilicate ceramics. Color stability is a critical factor in long-term esthetic success of dental restorations, especially in the anterior region. A comprehensive electronic search was performed in PubMed, Web of Science, and Scopus databases, to identify relevant in vitro studies published between 2015 and January 2025. Eligible studies directly compared polished and glazed lithium disilicate ceramics, and reported color change using ΔE values with extractable statistical data. Data synthesis was conducted using a random-effects model, and heterogeneity was assessed using I² and t² statistics. Methodological quality of included studies was evaluated using a QUIN tool. Out of 478 initially identified studies, 83 were included in the qualitative synthesis, and 8 met the inclusion criteria for the quantitative meta-analysis. The pooled analysis showed that polished lithium disilicate specimens demonstrated significantly greater color change over time than glazed ones (SMD = 1.81, 95% CI: 0.67-2.95, p = 0.007). High heterogeneity was detected (I² = 93%), largely attributed to variations in aging protocols and measurement techniques. Glazing significantly improves the long-term color stability of lithium disilicate ceramics, making it the preferred surface treatment in esthetically demanding cases.